Radial Approach in the Treatment of Supraaortic Arterial Lesions - Théron, J. (Centauro S.r.l., 2007)
Radial approach (mainly right) has been used in the treatment of 67 supraaortic lesions including 56 carotid, nine vertebral and two subclavian artery stenoses. This approach offers new possibilities and solves most of the remaining technical difficulties or impossibilities encountered in the endovascular treatment of supraaortic lesions. The current technique is described. The results of this first series have been very satisfactory without complication. MR angiography allows selection of patients suitable for radial approach.